Solid electrolytic capacitor
By controlling the glass transition temperature and hardness of the resin in the outer body of the solid electrolytic capacitor, the problem of reducing the sealing property of the outer body at high temperature is solved, high sealing and heat resistance are achieved, and the service life of the capacitor is extended.
Patent Information
- Application Number
- CN202380041614.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2024-12-31
AI Technical Summary
Solid electrolytic capacitors tend to reduce the sealing properties of the outer body due to thermal expansion and heat shrinkage at high temperatures, resulting in cracks and peeling, and the prior art is difficult to effectively suppress these problems.
By measuring the loss modulus and hardness in the exterior body by using the nano-indentation method, the glass transition temperature Tg of the resin is controlled to be less than 140°C, and the hardness of the resin is reduced to 0.08 GPa or less within a temperature range of 260°C or less than Tg. Relax stress and improve sealing.
High sealing and excellent heat resistance of the exterior body at high temperatures are achieved, reducing the electrostatic capacity and increasing the equivalent series resistance are suppressed, and the service life of the solid electrolytic capacitor is extended.
Smart Images

Figure CN119234286A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolytic capacitor. Background Art
[0002] Solid electrolytic capacitors have low equivalent series resistance (ESR) and excellent frequency characteristics, so they are used in various electronic devices. Solid electrolytic capacitors include: capacitor elements, lead terminals electrically connected to the capacitor elements, and an outer casing that seals a portion of the lead terminals and the capacitor elements. By using a solid conductive polymer as the electrolyte contained in the capacitor element, the solid electrolytic capacitor shows low ESR and excellent frequency characteristics.
[0003] Solid electrolytic capacitors are usually soldered to the substrate through a reflow process exposed to high temperature. At this time, cracks are sometimes formed on the outer body due to thermal stress, and the sealing of the outer body is reduced. When the sealing is reduced, the conductive polymer contained in the solid electrolyte layer is oxidized and degraded due to the intrusion of moisture or oxygen into the interior of the solid electrolytic capacitor. As a result, the conductivity of the solid electrolyte layer is reduced, which will cause a decrease in the electrostatic capacitance of the solid electrolytic capacitor and an increase in the ESR. Therefore, various solid electrolytic capacitors are proposed for the purpose of improving the sealing of the outer body.
[0004] For example, Patent Document 1 discloses: "A solid electrolytic capacitor comprising: a capacitor element comprising a sintered porous anode body, a dielectric disposed on the anode body, and a solid electrolyte disposed on the dielectric; an anode lead extending from a surface of the capacitor element; an anode terminal electrically connected to the anode lead and a cathode terminal electrically connected to the solid electrolyte; and a shell material encapsulating the capacitor element and the anode lead, formed from a curable resin matrix having a thermal expansion coefficient of about 42 ppm / °C or less at a temperature higher than the glass transition temperature of the resin matrix, wherein the capacitor shows an initial equivalent series resistance of about 200 milliohms or less measured at an operating frequency of 100 kHz and a temperature of 23°C, and the ratio of the equivalent series resistance of the capacitor after exposure to a temperature of 125°C for 560 hours to the initial equivalent series resistance of the capacitor is about 2.0 or less.".
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2021-528851 Summary of the invention
[0008] Problem that the invention aims to solve
[0009] At high temperatures, thermal expansion and contraction of the outer casing, capacitor element, lead terminals, etc. occur inside the solid electrolytic capacitor. The outer casing seals the capacitor element and part of the lead terminals, so stress from the capacitor element and lead terminals is also applied to the outer casing. Therefore, cracks are easily formed inside the outer casing. At the same time, cracks and peeling are also easily formed at the interface between the outer casing and the capacitor element and the interface between the outer casing and the lead terminals.
[0010] In order to suppress the formation of cracks and peeling caused by these internal stresses and improve the sealing of the outer body, there are also methods to reduce the thermal expansion and thermal contraction of the outer body as in the prior art. However, due to the relationship between the thermal expansion coefficient of the outer body and the thermal expansion coefficient of the capacitor element and the lead terminal as adherends, the internal stress may increase, and the methods of the prior art are insufficient as technical measures. Therefore, it is important to stipulate the material properties of the outer body that contribute to the internal stress alone, that is, the elastic modulus and hardness of the outer body, in order to suppress cracks and peeling generated at the interface between the outer body and the capacitor element and the lead terminal and improve the sealing.
[0011] Under such circumstances, an object of the present disclosure is to provide a solid electrolytic capacitor having a high sealing property of an exterior body and excellent heat resistance even at high temperatures.
[0012] Solutions for solving problems
[0013] The present disclosure relates to a solid electrolytic capacitor. The solid electrolytic capacitor is a solid electrolytic capacitor comprising a capacitor element, a lead terminal electrically connected to the capacitor element, and an outer casing that seals a portion of the lead terminal and the capacitor element, the outer casing comprising a resin portion containing a resin, and when the temperature at which the loss modulus measured by nano-level dynamic viscoelasticity measurement using a nanoindentation method changes from an increase to a decrease in the resin portion is set as the glass transition temperature Tg of the resin, the glass transition temperature Tg is 140°C or less, and within a temperature range of more than the glass transition temperature Tg and less than 260°C, the hardness of the resin portion measured by the nanoindentation method is 0.08 GPa or less.
[0014] As long as the combination is possible, the contents of two or more claims arbitrarily selected from the plurality of claims described in the appended claims may be combined. In addition, as long as the combination is possible, the configurations described in the embodiments may be arbitrarily combined.
[0015] Effects of the Invention
[0016] According to the present disclosure, a solid electrolytic capacitor having excellent heat resistance can be obtained.
[0017] While the novel features of the present invention are described in the appended claims, the present invention will be better understood from the following detailed description both as to structure and content and in conjunction with other objects and features of the present invention and with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a longitudinal cross-sectional view schematically showing a solid electrolytic capacitor according to one embodiment of the present disclosure.
[0019] Figure 2 This is a graph showing the relationship between the temperature and the loss modulus of the resin contained in the outer casing of the solid electrolytic capacitor.
[0020] Figure 3 This is a graph showing the relationship between the temperature and hardness of the resin portion included in the outer casing of the solid electrolytic capacitor. DETAILED DESCRIPTION
[0021] The following examples illustrate the embodiments of the present disclosure, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes illustrated, but other numerical values and materials can also be used as long as the invention to which the present disclosure relates can be implemented. In this specification, the description of "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "above numerical value A and below numerical value B". In the following description, when the lower limit and upper limit of numerical values related to specific physical properties, conditions, etc. are illustrated, as long as the lower limit is not above the upper limit, any of the exemplified lower limits and any of the exemplified upper limits can be arbitrarily combined.
[0022] The solid electrolytic capacitor involved in the present embodiment includes: a capacitor element, a lead terminal electrically connected to the capacitor element, and an outer casing that seals a portion of the lead terminal and the capacitor element. The outer casing includes a resin portion containing a resin. Hereinafter, the resin is sometimes referred to as "resin (R)". When the temperature at which the loss modulus measured by the nanoscale dynamic viscoelasticity measurement using the nanoindentation method changes from an increase to a decrease in the resin portion is set as the glass transition temperature Tg of the resin (R), the glass transition temperature Tg is 140°C or less. In addition, within a temperature range of above the glass transition temperature Tg and below 260°C, the hardness of the resin portion measured by the nanoindentation method (in other words, the hardness obtained when the resin portion is measured by the nanoindentation method) is 0.08GPa or less. In another embodiment, within a temperature range of above 140°C and below 260°C, the hardness of the resin portion measured by the nanoindentation method can be 0.08GPa or less.
[0023] As described above, in order to improve the heat resistance of solid electrolytic capacitors, it is important to suppress cracks and peeling generated at the interface between the outer casing and the capacitor element and the lead terminal. As a result of the study, the present inventors have newly discovered that in the outer casing, by controlling the glass transition temperature Tg of the resin (R) contained in the outer casing and the hardness of the resin portion containing the resin (R), the stress applied to the outer casing by the capacitor element and the lead terminal is relaxed.
[0024] When the temperature of the resin having a glass transition temperature Tg is increased, the resin (R) contained in the outer casing of the solid electrolytic capacitor according to the present embodiment changes from a glass state to a rubber state at the glass transition temperature Tg. The glass transition temperature Tg of the resin (R) contained in the outer casing of the solid electrolytic capacitor according to the present embodiment is 140°C or less, and the resin (R) becomes a rubber state in a temperature range of above the glass transition temperature Tg and below 260°C. In addition, within this temperature range, the hardness of the resin portion containing the resin (R) measured by the nanoindentation method is as low as 0.08 GPa or less.
[0025] Solid electrolytic capacitors are usually exposed to high temperatures (e.g., temperatures in the range of 180°C to 260°C) during the reflow soldering process, etc. In addition, solid electrolytic capacitors are sometimes used at high temperatures. When a solid electrolytic capacitor is exposed to high temperatures, the components of the solid electrolytic capacitor undergo thermal expansion. However, the thermal expansion coefficients of the components are different, so thermal stress is generated inside the solid electrolytic capacitor. As a result, when previous solid electrolytic capacitors were exposed to high temperatures, cracks and peeling were easily generated at the interface between the outer casing and the capacitor element, and at the interface between the outer casing and the lead terminal.
[0026] When the solid electrolytic capacitor involved in the present embodiment is exposed to a temperature above the glass transition temperature Tg, the resin (R) contained in the outer body becomes a rubber state, and the hardness of the resin portion containing the resin (R) is as low as 0.08GPa or less. Therefore, the outer body can disperse and relax the stress applied to the outer body by the capacitor element and the lead terminal to the outer body as a whole. As a result, the generation of cracks inside the outer body can be suppressed, and cracks and peeling generated at the interface between the outer body and the capacitor element and the lead terminal can also be suppressed. As described above, the solid electrolytic capacitor involved in the present embodiment has high sealing performance of the outer body even at high temperatures and excellent heat resistance.
[0027] (Resin Department)
[0028] The resin portion contains a resin (R). The resin portion may be composed of only the resin (R), or may contain components other than the resin (R). Examples of components other than the resin (R) include a curing aid (curing accelerator), a low stress agent (flexibility agent), a release agent, a coupling agent, a colorant, an ion capture agent, and the like. The proportion of the resin (R) in the resin portion may be in the range of 70 to 100% by mass, in the range of 80 to 100% by mass, or in the range of 90 to 100% by mass.
[0029] (Resin(R))
[0030] The resin (R) contained in the resin portion may be composed of only one resin or may contain multiple resins. When the resin (R) contains multiple resins, 50% by mass or more of the resins constituting the resin (R) may satisfy the above condition (glass transition temperature Tg). Preferably, all the resins contained in the resin (R) satisfy the above condition (glass transition temperature Tg).
[0031] The glass transition temperature Tg of the resin (R) can be obtained by nano-scale dynamic viscoelasticity measurement (nano DMA) using the nanoindentation method. For example, it is obtained by cutting out a portion of the outer body and performing the measurement on the resin portion of its cross section. The details of an example of the measurement method are described by way of an embodiment. In the case where the resin portion contains a filler, the triangular pyramid indenter is brought into contact with a portion where no filler is present for measurement. When the loss modulus of the resin (R) at each temperature is measured while the temperature is increased, a decreasing behavior can be observed after the loss modulus increases. At this time, the temperature at which the loss modulus changes from an increase to a decrease is set as the glass transition temperature Tg. That is, by using the nano-scale dynamic viscoelasticity measurement using the nanoindentation method, when the loss modulus of the resin portion is measured while the temperature is increased, the temperature at which the loss modulus changes from an increase to a decrease is set as the glass transition temperature Tg of the resin (R). It should be noted that the loss modulus can be determined, for example, by performing a dynamic viscoelasticity measurement on any 5 locations of the resin portion and obtaining the average value of the measured values.
[0032] The glass transition temperature Tg of the resin (R) may be 125° C. or lower. When the glass transition temperature Tg of the resin (R) is 125° C. or lower, the outer casing can relax stress in a wide temperature range and maintain high sealing properties.
[0033] The glass transition temperature Tg depends on the type, structure, crosslinking density, etc. of the resin. For example, the glass transition temperature Tg tends to decrease by reducing the crosslinking density of the resin.
[0034] The hardness of the resin portion containing resin (R) is also measured by nanoindentation in the same manner as the glass transition temperature of resin (R). For example, it can be obtained by cutting out a portion of the outer casing and continuously measuring the rigidity of the resin portion of its cross section. The details of an example of the measuring method are described by an embodiment. In the case where the resin portion contains a filler, the triangular pyramid indenter is brought into contact with a portion where no filler is present for measurement. The hardness can be determined, for example, by measuring any 5 locations of the resin portion and finding the average value of the measured values. From the perspective of fully relaxing the stress received by the outer casing from the capacitor element and the lead terminal at high temperatures and maintaining high sealing properties, the hardness of the resin portion within a temperature range of above the glass transition temperature Tg and below 260°C can be 0.05GPa or less, or 0.03GPa or less. In another embodiment, the hardness of the resin portion within a temperature range of above 140°C and below 260°C can be 0.05GPa or less, or 0.03GPa or less.
[0035] Similar to the glass transition temperature Tg, the hardness of the resin portion can be changed by changing the type, structure, crosslinking density, etc. of the resin (R). For example, when the distance between crosslinking points of the resin (R) contained in the resin portion is increased, the hardness tends to decrease.
[0036] The resin (R) is not particularly limited as long as it has the above-mentioned properties, and may be, for example, a thermosetting resin or a thermoplastic resin.
[0037] Examples of the thermosetting resin include epoxy resins, phenolic resins, urea resins, polyimide resins, polyamideimide resins, polyurethane resins, diallyl phthalate resins, and unsaturated polyester resins. The resin (R) may be used alone or in combination of two or more.
[0038] As the thermoplastic resin, for example, polyphenylene sulfide (PPS), polybutylene terephthalate (PBT), etc. may be used. As the resin (R), one of these resins may be used alone, or two or more of them may be used in combination.
[0039] Resin (R) may include epoxy resin or may be epoxy resin. Epoxy resin has excellent electrical insulation, water resistance, chemical resistance, etc., and it is easy to control the glass transition temperature Tg of resin (R) and the hardness of resin portion. Epoxy resin is usually obtained by cross-linking reaction of a main agent of a monomer or polymer (prepolymer) having an epoxy group with a curing agent. As a main agent, prepolymers such as polyaromatic ring epoxy resin, biphenyl type epoxy resin, cresol novolac type epoxy resin, dicyclopentadiene type epoxy resin can be used. It should be noted that polyaromatic ring epoxy resin is an epoxy resin having multiple polycyclic aromatic rings on the main skeleton. Polyaromatic ring epoxy resin has low viscosity at high temperature. Therefore, for example, when sandblasting is applied to the lead terminal, the bonding strength between the outer casing containing polyaromatic ring epoxy resin and the lead terminal becomes physically high due to the anchoring effect.
[0040] When the resin (R) contains epoxy resin, the glass transition temperature Tg of the resin (R) depends on the crosslinking density, structure, etc. of the epoxy resin. Therefore, the glass transition temperature Tg can be controlled by the type of the main agent and the curing agent, the ratio of the main agent to the curing agent, the molecular weight of the main agent, etc. For example, when the concentration of the functional group (epoxy group) of the main agent is low or the epoxy equivalent of the main agent is low, the crosslinking density of the epoxy resin becomes smaller and the glass transition temperature Tg tends to become lower. In addition, if it is a main agent with the same skeleton structure, the fewer the number of nuclei, the fewer the number of functional groups, the smaller the crosslinking density of the epoxy resin, and the glass transition temperature Tg tends to become lower. Similarly, if it is a main agent with the same degree of epoxy equivalent, the fewer the number of nuclei, the fewer the number of functional groups, the smaller the crosslinking density of the epoxy resin, and the glass transition temperature Tg tends to become lower. On the other hand, when the skeleton structure of the epoxy resin is rigid or symmetric, the glass transition temperature Tg tends to become higher. Likewise, when the epoxy resin has a bulky substituent, the glass transition temperature Tg tends to be higher.
[0041] The curing agent is not particularly limited and can be appropriately selected according to the type of the main agent. As the curing agent, polyfunctional or polyaromatic novolac curing agents such as phenol novolac, anhydride curing agents such as tetrahydrophthalic anhydride and hexahydrophthalic anhydride, amine curing agents such as ethylenediamine and aromatic amines can be listed. In order to make the main agent and the curing agent react to obtain resin (R), in addition to the main agent and the curing agent, polymerization initiators, catalysts, etc. can also be used. Polymerization initiators, catalysts, etc. can also be appropriately selected according to the type of the main agent. As catalysts, phosphorus compounds such as triphenylphosphine and modified products thereof, amines, imidazoles, etc. can be listed.
[0042] (filler)
[0043] The outer casing may further include fillers dispersed in the resin portion. The outer casing may be composed of a resin portion and fillers dispersed in the resin portion. The fillers are dispersed in the resin portion containing the resin (R). There is no particular limitation on the filler, and known fillers can be used. For example, insulating fillers such as insulating particles and insulating fibers are used. Insulating materials constituting the insulating fillers include, for example, insulating compounds such as silica, alumina, aluminum nitride, boron nitride, glass, mineral materials (talc, mica, clay, etc.), etc. The filler contained in the outer casing may be one kind or two or more kinds.
[0044] When the content of filler in the outer body is high, the strength of the outer body becomes higher and the shrinkage rate during molding also becomes lower. In addition, the hygroscopicity becomes lower and the flame retardancy becomes higher. On the other hand, when the content of filler is low, the adhesion of the outer body to the capacitor element and the lead terminal becomes higher. In addition, the elasticity of the outer body becomes lower and the measured hardness tends to become lower. In addition, when the content of filler is low, the resin part is easily filled in the gap between the capacitor element and the lead terminal. In addition, in the case of containing multiple capacitor elements, it is also easy to fill in the gap between the capacitor elements. In order to achieve these characteristics in a balanced manner, the content of filler in the outer body is preferably in the range of 75 mass % to 90 mass %. In addition, the content can be greater than 78 mass % and can be less than 86 mass %.
[0045] When the content rate of the filler in the outer body is the same, in the outer body with a small particle size of the filler, the resin (R) present between the fillers acts as a buffer material and is easy to relax stress. As a result, the stress that can be relaxed by the outer body as a whole becomes larger. In addition, when the particle size of the filler is small, the resin portion is easily filled in the gap between the capacitor element and the lead terminal. In addition, in the case of containing multiple capacitor elements, it is also easy to fill in the gap between the capacitor elements. Therefore, the maximum particle size of the filler can be less than 100μm (for example, less than 55μm). By making the maximum particle size less than 55μm, as described above, it is easy to relax stress. Among them, the maximum particle size refers to the particle size of the largest particle among the filler particles contained in the outer body. The maximum particle size is obtained by photographing the cross section of the outer body, arbitrarily selecting 100 particles, and measuring the cross-sectional area of the particles. In an equivalent circle having the same area as the cross-sectional area of each particle, the diameter of the largest equivalent circle becomes the maximum particle size.
[0046] The solid electrolytic capacitor involved in this embodiment has high heat resistance and can maintain the sealing of the outer body even at high temperatures. Therefore, it is possible to suppress the intrusion of moisture and oxygen into the solid electrolytic capacitor, and it is not easy to cause the deterioration of the conductive polymer in the solid electrolyte contained in the capacitor element. Therefore, even if exposed to high temperatures, the electrostatic capacitance and ESR of the solid electrolytic capacitor can be maintained.
[0047] The average value of the capacitance change rate represented by the following formula may be -5.0% or more.
[0048] Capacitance change rate (%) = 100 × (C1-C0) / C0
[0049] (Where C0 is the initial capacitance, C1 is the capacitance after heating at 125°C for 7000 hours)
[0050] The average value may be greater than -3.0% or greater than -1.0%. The average value is the average value of the capacitance change rate of at least 60 (e.g., 100) solid electrolytic capacitors. The capacitance may be measured, for example, using an LCR tester. The capacitance change rate of a solid electrolytic capacitor is preferably greater than -5.0%, more preferably greater than -3.0%.
[0051] The solid electrolytic capacitor involved in this embodiment includes a capacitor element, a lead terminal, and an outer casing, and includes other components as needed. Below, an example of the structure of a solid electrolytic capacitor is described. Among them, the structure of the solid electrolytic capacitor is not limited to the following example. For structures other than the characteristic structure of the solid electrolytic capacitor involved in this embodiment, a known structure may also be adopted. It should be noted that in addition to the above-mentioned outer casing, the solid electrolytic capacitor may also include a shell formed of metal or the like.
[0052] [Capacitor elements]
[0053] The solid electrolytic capacitor has one or more capacitor elements. It should be noted that the number of capacitor elements contained in the solid electrolytic capacitor is determined according to the purpose. When more than two capacitor elements are included, the capacitor elements are usually stacked. In this case, the anode lead terminal is connected to the anode stacking part stacked with multiple anode parts, and the cathode lead terminal is connected to the cathode stacking part stacked with multiple cathode parts.
[0054] (Anode)
[0055] The anode body may contain a valve metal, an alloy containing a valve metal, a compound containing a valve metal, and the like. These materials may be used alone or in combination of two or more. As the valve metal, for example, aluminum, tantalum, niobium, and titanium are preferably used. The surface of the anode body may have a porous structure. For example, a porous structure is obtained by roughening the surface of a valve metal-containing substrate (a foil-shaped or plate-shaped substrate, etc.) by etching or the like. In addition, the anode body may be a molded body of particles containing a valve metal or a sintered body thereof. In the case where the anode body is a sintered body, the anode portion may include a portion of an anode wire buried in the sintered body. In this case, one end of the anode lead terminal is connected to the anode wire.
[0056] (Dielectric layer)
[0057] The dielectric layer is an insulating layer formed in a manner covering at least a portion of the surface of the anode body. There is no particular limitation as long as it functions as a dielectric layer. For example, it is formed by anodizing the valve metal on the surface of the anode body by chemical conversion treatment or the like. In this case, the dielectric layer includes an oxide of the valve metal. For example, when tantalum is used as the valve metal, the dielectric layer includes Ta. 2 O 5 When aluminum is used as the valve metal, the dielectric layer contains Al 2 O 3 .
[0058] (Solid electrolyte layer)
[0059] The solid electrolyte layer is formed in a manner covering at least a portion of the dielectric layer. The solid electrolyte layer includes a conductive polymer. As the conductive polymer, polypyrrole, polythiophene, polyfuran, polyaniline, polyacetylene, polyphenylene, polyphenylene vinylene, polyacene, polythiophene vinylene and their derivatives can be used. As a derivative, for example, poly(3,4-ethylenedioxythiophene) and the like are included.
[0060] A dopant may be added to the conductive polymer. The dopant may be selected according to the conductive polymer, or a known dopant may be used. Examples of the dopant include naphthalenesulfonic acid, p-toluenesulfonic acid, polystyrenesulfonic acid, and salts thereof.
[0061] The solid electrolyte layer containing the conductive polymer can be formed by polymerizing a monomer as a raw material on the dielectric layer. Alternatively, the solid electrolyte layer can be formed by placing a liquid containing the conductive polymer on the dielectric layer and then drying it.
[0062] (Cathode extraction layer)
[0063] The cathode lead-out layer may include a first layer covering at least a portion of the solid electrolyte layer, or may include a first layer and a second layer covering the first layer. Both the first layer and the second layer are conductive layers. The first layer is formed, for example, by a layer containing conductive particles, a metal foil, etc. As conductive particles, for example, conductive carbon, metal powder, etc. may be listed. In addition, the second layer is formed, for example, by a layer containing metal powder or a metal foil, etc. The layer containing metal powder is formed, for example, using a composition (metal paste) containing metal powder such as silver particles and a resin (binder resin).
[0064] (Adhesive layer)
[0065] The adhesive layer connects the cathode lead terminal and the cathode portion. The adhesive layer contains conductive particles. Examples of the conductive particles include metal particles (eg, silver particles). The adhesive layer is formed using a metal paste containing metal particles and a resin.
[0066] [Lead terminal]
[0067] The lead terminal includes an anode lead terminal and a cathode lead terminal. One end side of the anode lead terminal and the cathode lead terminal is sealed by the outer casing together with the capacitor element. One end of the anode lead terminal is electrically connected to the anode portion of the capacitor element, and the other end is exposed to the outside of the outer casing. One end of the cathode lead terminal is electrically connected to the cathode portion of the capacitor element, and the other end is exposed to the outside of the outer casing. The anode lead terminal and the cathode lead terminal exposed from the outer casing are used for welding with the substrate to be mounted with the solid electrolytic capacitor, etc.
[0068] As the anode lead terminal and the cathode lead terminal, the lead terminal commonly used in the solid electrolytic capacitor can be used without particular limitation. As the raw material, for example, metals such as copper or their alloys can be listed. The surface of the anode lead terminal and the cathode lead terminal can also be subjected to sandblasting. By sandblasting, the adhesion strength between the lead terminal and the outer body is improved, so it is difficult to produce cracks and peeling at the interface.
[0069] [Exterior body]
[0070] The outer casing seals the capacitor element and a part of the anode lead terminal and the cathode lead terminal. The outer casing described above is used as the outer casing.
[0071] The outer casing can be formed using molding techniques such as injection molding, insert molding, and compression molding. In molding, an uncured resin mixture is used. For example, a resin mixture containing a main agent (monomer, prepolymer, etc.) as a raw material of the resin (R), a curing agent, and a filler is used. For example, a predetermined mold is used to fill the resin mixture in a predetermined position in a manner covering one end of the capacitor element and the lead terminal. Through molding, the resin mixture is cured to form an outer casing containing a resin portion containing the resin (R).
[0072] The manufacturing method of the solid electrolytic capacitor involved in this embodiment is not particularly limited, and a known process can be used. For example, the capacitor element is manufactured by a manufacturing method having the following steps: a step of forming a dielectric layer in a manner covering at least a portion of the anode body; a step of forming a solid electrolyte layer in a manner covering at least a portion of the dielectric layer; and a step of forming a cathode lead layer on at least a portion of the solid electrolyte layer. The step of forming the cathode lead layer includes, for example, a step of forming a carbon layer and a step of forming a silver paste layer on at least a portion of the carbon layer. In addition, before the step of forming the dielectric layer, there may also be a step of preparing the anode body.
[0073] Solid electrolytic capacitors are manufactured, for example, by a manufacturing method including a step of electrically connecting lead terminals to capacitor elements and a step of covering the capacitor elements and a portion of the lead terminals with an outer casing (sealing step). Solid electrolytic capacitors may be wound, chip-type, or laminated.
[0074] use Figure 1 The configuration of an example of the solid electrolytic capacitor according to the present embodiment will be described. The above-described configuration elements can be applied to the configuration elements of the example described below. In addition, the configuration elements of the example described below can be changed according to the above description.
[0075] Figure 1 This is a cross-sectional view briefly showing the structure of a solid electrolytic capacitor 1 according to an example of the present embodiment. The solid electrolytic capacitor 1 includes a capacitor element 2, lead terminals (anode lead terminal 4 and cathode lead terminal 5), and an outer casing 3 that seals a portion of the lead terminals and the capacitor element 2. A portion of the anode lead terminal 4 and a portion of the cathode lead terminal 5 are exposed from the outer casing 3. As the outer casing 3, the outer casing described above is used.
[0076] Capacitor element 2 includes anode body 6 constituting an anode portion, dielectric layer 7 covering anode body 6 , and cathode portion 8 covering dielectric layer 7 .
[0077] The anode body 6 includes a region facing the cathode portion 8 and a region not facing the cathode portion 8. In the region not facing the cathode portion 8 of the anode body 6, an insulating separation layer 13 is formed in a band-shaped manner to cover the surface of the anode body 6 and restrict the contact between the cathode portion 8 and the anode body 6. The other portion of the region not facing the cathode portion 8 of the anode body 6 is electrically connected to the anode lead terminal 4 by welding. The cathode lead terminal 5 is electrically connected to the cathode portion 8 via an adhesive layer 14 formed of a conductive adhesive.
[0078] Cathode portion 8 includes solid electrolyte layer 9 covering dielectric layer 7 and cathode lead layer 10 covering solid electrolyte layer 9. Cathode lead layer 10 includes carbon layer 11 and silver paste layer 12.
[0079] (Note)
[0080] The above description discloses the following technology.
[0081] (Technology 1)
[0082] A solid electrolytic capacitor comprising: a capacitor element, a lead terminal electrically connected to the capacitor element, and an outer casing sealing a portion of the lead terminal and the capacitor element.
[0083] The outer casing includes a resin portion containing a resin,
[0084] When the temperature at which the loss modulus measured by nanoscale dynamic viscoelasticity measurement using a nanoindentation method in the resin portion changes from increasing to decreasing is defined as the glass transition temperature Tg of the resin, the glass transition temperature Tg is 140° C. or less,
[0085] In a temperature range of not less than the glass transition temperature Tg and not more than 260° C., the hardness of the resin portion measured by a nanoindentation method is not more than 0.08 GPa.
[0086] (Technique 2)
[0087] The solid electrolytic capacitor according to technology 1, wherein the glass transition temperature Tg of the resin is 125° C. or less.
[0088] (Technique 3)
[0089] The solid electrolytic capacitor according to technology 1 or 2, wherein the resin is an epoxy resin.
[0090] (Technique 4)
[0091] The solid electrolytic capacitor according to any one of techniques 1 to 3, wherein the outer casing further includes a filler dispersed in the resin portion.
[0092] (Technique 5)
[0093] In the solid electrolytic capacitor according to technology 4, the content rate of the filler in the outer casing is within a range of 75 mass % to 90 mass %.
[0094] (Technique 6)
[0095] The solid electrolytic capacitor according to technology 4 or 5, wherein the maximum particle size of the filler is 55 μm or less.
[0096] (Technique 7)
[0097] A solid electrolytic capacitor according to any one of techniques 1 to 6, wherein:
[0098] The average value of the electrostatic capacitance change rate expressed by the following formula is -5.0% or more,
[0099] Capacitance change rate (%) = 100 × (C1-C0) / C0
[0100] (Where C0 is the initial electrostatic capacitance, and C1 is the electrostatic capacitance after heating at 125°C for 7000 hours).
[0101] Example
[0102] Hereinafter, the present disclosure will be specifically described based on examples, but the present disclosure is not limited to the following examples. In this example, solid electrolytic capacitors having different outer packages were produced and their heat resistance was evaluated.
[0103] (1) Fabrication of solid electrolytic capacitors A1, B1, and B2
[0104] Solid electrolytic capacitors A1, B1 and B2 were manufactured according to the following procedure.
[0105] (1-1) Fabrication of capacitor elements
[0106] (1-a) Preparation of anode body
[0107] An anode body was prepared by etching both surfaces of an aluminum foil (thickness: 100 μm).
[0108] (1-b) Formation of dielectric layer
[0109] The anode body was immersed in a phosphoric acid solution (liquid temperature 70° C.) with a concentration of 0.3 mass %, and a DC voltage of 70 V was applied for 20 minutes to form a layer containing aluminum oxide (Al 2 O 3 ) dielectric layer.
[0110] (1-c) Formation of Solid Electrolyte Layer
[0111] In the anode body having a dielectric layer formed therein, a separation portion is formed by pasting an insulating resist tape between an area where a solid electrolyte layer is formed and an area where a solid electrolyte layer is not formed. An aqueous solution containing a pyrrole monomer and p-toluenesulfonic acid is prepared. The concentration of the pyrrole monomer in the aqueous solution is 0.5 mol / L, and the concentration of p-toluenesulfonic acid is 0.3 mol / L. The anode body having a dielectric layer formed therein in (1-b) above and the counter electrode are immersed in the obtained aqueous solution. In this state, a solid electrolyte layer is formed by electrolytic polymerization at a polymerization voltage of 3 V (polymerization potential relative to a silver reference electrode) at 25°C.
[0112] (1-d) Formation of cathode lead layer
[0113] The anode body obtained in (1-c) was immersed in a dispersion in which graphite particles were dispersed in water. The dispersion applied to the anode body was then dried to form a carbon layer on the surface of the solid electrolyte layer. Drying was performed at 150° C. for 30 minutes.
[0114] Next, a silver paste containing silver particles and a binder resin (epoxy resin) is applied to the surface of the carbon layer, and heated at 150°C for 30 minutes to cure the binder resin and form a silver paste layer. In this way, a cathode lead layer consisting of a carbon layer and a silver paste layer is formed, and a cathode portion including a solid electrolyte layer and a cathode lead layer is formed. Through steps (1-a) to (1-d), a capacitor element is produced.
[0115] (1-2) Assembly of solid electrolytic capacitors
[0116] The cathode portion of the capacitor element obtained in (1-d) was bonded to one end of a cathode lead terminal via an adhesive layer using a conductive adhesive. One end of an anode body protruding from the capacitor element was bonded to one end of an anode lead terminal by laser welding.
[0117] Next, an outer casing is formed around the capacitor element and the lead terminal using the following resin mixtures 1 to 3 by molding. At this time, the other end of the anode lead terminal and the other end of the cathode lead terminal are exposed from the outer casing. In this way, solid electrolytic capacitors A1, B1 and B2 are completed. It should be noted that as the material of the outer casing, the following resin mixture 1 is used in the solid electrolytic capacitor A1, the following resin mixture 2 is used in the solid electrolytic capacitor B1, and the following resin mixture 3 is used in the solid electrolytic capacitor B2. The resin portion of the outer casing formed by the resin mixture 1 contains a polyaromatic epoxy resin as a resin (R). It should be noted that fillers are dispersed in the following resin mixtures.
[0118] The resin mixture 1 is a resin mixture in which the glass transition temperature Tg of the resin portion formed by curing measured by nanoDMA is about 125° C., and the hardness of the resin portion is 0.08 or less in a temperature range higher than the glass transition temperature Tg.
[0119] Resin mixture 2 is a resin mixture in which, in a resin portion formed by curing, the glass transition temperature Tg measured by nanoDMA is about 145° C., and the hardness of the resin portion is greater than 0.08 in a temperature range higher than the glass transition temperature Tg.
[0120] Resin mixture 3 is a resin mixture in which the glass transition temperature Tg of the resin portion formed by curing measured by nanoDMA is about 165° C., and the hardness of the resin portion is greater than 0.08 in a temperature range higher than the glass transition temperature Tg.
[0121] (2) Evaluation
[0122] The solid electrolytic capacitors A1, B1, and B2 prepared in (1) were evaluated as follows.
[0123] (2-1) Evaluation of outer casing
[0124] (2-a) Glass transition temperature Tg of resin
[0125] A portion of the outer casing of the solid electrolytic capacitors A1, B1 and B2 was cut out and used as a sample. For 5 portions of the sample that do not contain fillers in the cross section, the nano-level dynamic viscoelasticity measurement (nano-DMA) using the nanoindentation method was performed as described above. Specifically, the nano-level dynamic viscoelasticity (especially the loss modulus) at room temperature (25°C), 85°C, 105°C, 125°C, 145°C, 165°C, and 260°C was measured using Triboindenter TI950 manufactured by Hysitron. The measurement was performed by heating the sample in stages under a nitrogen atmosphere. Specifically, the sample was heated at a heating rate of 20°C / min, and after reaching the measurement temperature, the temperature was maintained for 20 minutes, and then the measurement was performed at the measurement temperature. The measurement frequency was 100Hz. The nano-level dynamic viscoelasticity measurement was performed by the following method. A diamond triangular pyramid indenter (Berkovich indenter) was brought into contact with the portion (resin portion) that does not contain fillers in the cross section of the sample, and the indenter was vibrated slightly. The response amplitude and phase difference to the vibration are obtained as a function of time, and the stiffness and sample damping are calculated. The loss modulus is calculated using the calculated sample damping results at each temperature. The loss modulus at each temperature is determined by averaging the measured values at 5 locations. The results are shown in Figure 1. Figure 2 shown.
[0126] When the temperature rises from 25°C to 260°C, the loss modulus increases and then decreases. The point where the loss modulus changes from increasing to decreasing is defined as the glass transition temperature Tg. The glass transition temperatures Tg of the resin contained in the outer casings of the solid electrolytic capacitors A1, B1, and B2 are 125°C, about 145°C (temperature in the range of 145°C to 165°C), and 165°C, respectively.
[0127] (2-b) Hardness of the resin part
[0128] A portion of the outer casing of the solid electrolytic capacitors A1, B1 and B2 was cut out and used as a sample. For 5 locations of the resin portion of the cross section of the sample, the hardness at room temperature (25°C), 85°C, 105°C, 125°C, 145°C, 165°C, and 260°C was measured by a continuous rigidity measurement method using a nanoindentation method. The measurement was performed using the above-mentioned device using the above-mentioned temperature increase method. The hardness was measured by the following method. In the portion of the cross section of the sample that does not contain filler (resin portion), an indentation load and unloading test in which the load and indentation depth were continuously measured was performed using a diamond triangular pyramid indenter (Berkovich indenter). Through these tests, a curve related to the load and indentation depth was obtained. The hardness is calculated using the projected area and load of the indentation remaining when the elastic deformation portion recovers after indentation. The hardness at each temperature is determined by finding the average of the measured values at 5 locations. The results are as follows. Figure 3 shown.
[0129] The hardness of the resin portion contained in the solid electrolytic capacitor A1 is 0.08 GPa or less in the temperature range of the glass transition temperature Tg (125°C) of the resin and 260°C or less. On the other hand, the hardness of the resin portion contained in the solid electrolytic capacitors B1 and B2 is a value higher than 0.08 GPa in the temperature range of the glass transition temperature Tg (resin of solid electrolytic capacitor B1: about 145°C, resin of solid electrolytic capacitor B2: 165°C) of the resin and 260°C or less.
[0130] From the above (2-a) and (2-b), it can be confirmed that the solid electrolytic capacitor A1 is a solid electrolytic capacitor according to the present embodiment. The solid electrolytic capacitors B1 and B2 are solid electrolytic capacitors of comparative examples.
[0131] (2-2) Evaluation of solid electrolytic capacitors
[0132] (2-c) Capacitance change rate
[0133] The change in electrostatic capacitance of the solid electrolytic capacitors A1, B1, and B2 at 125° C. was measured in the following procedure. 100 solid electrolytic capacitors A1, 60 solid electrolytic capacitors B1, and 60 solid electrolytic capacitors B2 were prepared.
[0134] In an environment of 20°C, using a 4-terminal LCR tester, the electrostatic capacitance (μF) of each solid electrolytic capacitor at a frequency of 120Hz is measured as the initial electrostatic capacitance C0 (μF). Then, each solid electrolytic capacitor is heated under the same temperature conditions as the reflow soldering process according to IPC / JEDEC J-STD-020D (the maximum temperature is 260°C, and heating is performed at 255°C or above for 30 seconds). Next, a high-temperature placement test is performed in which the solid electrolytic capacitor is placed for 7000 hours in an environment of 125°C. The electrostatic capacitance C1 (μF) of the solid electrolytic capacitor immediately after the heat treatment equivalent to the reflow soldering process (immediately after the reflow soldering) and the solid electrolytic capacitor after a specified time in the high-temperature placement test is measured in the same way as C0. Using the measured electrostatic capacitance, the rate of change of the electrostatic capacitance is calculated according to the following formula.
[0135] Capacitance change rate (%) = 100 × (C1-C0) / C0
[0136] The average value was calculated by taking the arithmetic average of the electrostatic capacitance change rate of 100 solid electrolytic capacitors A1. Similarly, the average value of the electrostatic capacitance change rate of 60 solid electrolytic capacitors B1 and the average value of the electrostatic capacitance change rate of 60 solid electrolytic capacitors B2 were calculated. The evaluation results are shown in Table 1. When the degradation of the solid electrolytic capacitor increases, the electrostatic capacitance change rate increases negatively. The closer the electrostatic capacitance change rate is to 0 (or the larger the positive value is), the less degradation of the solid electrolytic capacitor is.
[0137] [Table 1]
[0138]
[0139] As shown in Table 1, the average value of the electrostatic capacitance change rate of solid electrolytic capacitor A1 after the high-temperature placement test is greater than -5% (i.e., -5.0≤100×(C1-C0) / C0). It should be noted that when only the high-temperature placement test is performed without performing a heat treatment equivalent to the reflow process, the degradation of the solid electrolytic capacitor becomes less (i.e., the value of the electrostatic capacitance change rate further changes positively). On the other hand, the average value of the electrostatic capacitance change rate of solid electrolytic capacitors B1 and B2 after the high-temperature placement test is less than -5%. This means that solid electrolytic capacitor A1 is different from solid electrolytic capacitors B1 and B2, and the electrostatic capacitance decreases less even when exposed to high temperatures for a long time.
[0140] (2-d) ESR change rate
[0141] The change in ESR (equivalent series resistance) at 125° C. of the solid electrolytic capacitors A1 , B1 , and B2 was measured in the following procedure.
[0142] In an environment of 20°C, using a 4-terminal LCR tester, the ESR (mΩ) of each solid electrolytic capacitor at a frequency of 120kHz is measured as the initial ESR (E0) (mΩ). Then, each solid electrolytic capacitor is heated under the same temperature conditions as the reflow process according to IPC / JEDEC J-STD-020D (maximum temperature is 260°C, heating at 255°C or above for 30 seconds). The ESR (E1) (mΩ) after a specified time is measured using the same method as E0. Using the measured electrostatic capacitance, the rate of change of ESR is calculated according to the following formula.
[0143] ESR change rate (%) = 100 × (E1-E0) / E0
[0144] In addition, the ESR change rate of 100 solid electrolytic capacitors A1 was arithmetic averaged to obtain the average value. Similarly, the average value of the ESR change rate of 60 solid electrolytic capacitors B1 and the average value of the ESR change rate of 60 solid electrolytic capacitors B2 were obtained. The results are shown in Table 2. When the degradation of the solid electrolytic capacitor increases, the ESR change rate increases. The smaller the ESR change rate, the less degradation of the solid electrolytic capacitor.
[0145] [Table 2]
[0146]
[0147] As shown in Table 2, the ESR change rate of the solid electrolytic capacitor A1 is a significantly lower value than the ESR change rates of the solid electrolytic capacitors B1 and B2.
[0148] (2-e) Airtightness
[0149] The airtightness of solid electrolytic capacitors A1, B1 and B2 is evaluated in the following order. Heat each solid electrolytic capacitor for heat treatment under the same temperature conditions as the reflow soldering process according to IPC / JEDECJ-STD-020D (the maximum temperature is 260°C, and heating is performed at above 255°C for 30 seconds). Then, a temperature shock treatment is performed. Specifically, the temperature shock treatment is performed by placing each solid electrolytic capacitor in an environment of -55°C, and then repeating the operation of placing it in an environment of 125°C 100 times. A rough leak test is performed initially (before heat treatment), after heat treatment and after temperature shock treatment. Specifically, each solid electrolytic capacitor is placed in a small capsule, and the tiny pressure drop caused by the internal pressure in the small capsule leaking into the outer body is measured. In addition, the capacitor whose pressure change at this time is greater than the specified value is judged to be poorly airtight, and the airtight defect rate (%) is calculated.
[0150] 100 solid electrolytic capacitors A1, B1, and B2 were prepared, 100 of each, and the above test was carried out. The airtightness failure rate was calculated according to the following formula.
[0151] Airtightness failure rate (%) = 100 × (the number of solid electrolytic capacitors judged to be airtight) / (the number of solid electrolytic capacitors used in the test)
[0152] The airtightness failure rate of solid electrolytic capacitor A1, solid electrolytic capacitor B1 and solid electrolytic capacitor B2 at the initial stage, after heat treatment and after temperature shock treatment was calculated respectively. The results are shown in Table 3. In Table 3, the comprehensive airtightness failure rate refers to the ratio (%) of the total number of solid electrolytic capacitors judged to be airtight failure at the initial stage, after heat treatment and after temperature shock treatment to the number of solid electrolytic capacitors tested initially (solid electrolytic capacitor A1, solid electrolytic capacitor B1, solid electrolytic capacitor B2 are all 100).
[0153] [Table 3]
[0154]
[0155] As shown in Table 3, the airtightness of solid electrolytic capacitor A1 is high, and the airtightness is maintained even after heat treatment and temperature shock treatment. On the other hand, the airtightness of solid electrolytic capacitors B1 and B2 is confirmed to be reduced. In particular, it is clear that solid electrolytic capacitor B2 has defective airtightness at the beginning.
[0156] As described above, the solid electrolytic capacitor A1 is the solid electrolytic capacitor according to the present embodiment. It has been confirmed that the solid electrolytic capacitor A1 can suppress a decrease in capacitance and an increase in ESR even when exposed to high temperatures.
[0157] The resin contained in the outer casing of the solid electrolytic capacitor A1 becomes a rubber state at 125°C during the high temperature placement test, and the hardness of the resin portion containing the resin is also reduced to less than 0.08 GPa. Therefore, it can be considered that for the entire outer casing, the stress applied to the outer casing by the capacitor element and the lead terminal can be relaxed, the occurrence of cracks and peeling is suppressed, and the airtightness is improved. As a result, it can be inferred that the outer casing can maintain high sealing even at high temperatures.
[0158] On the other hand, it is believed that in the outer casings of the solid electrolytic capacitors B1 and B2, the stress applied to the outer casings was not sufficiently relaxed, and cracks and peeling occurred inside the outer casings and at the interfaces between the outer casings and the capacitor elements and lead terminals, resulting in reduced airtightness. It is believed that due to the reduced sealing of the outer casings, the conductivity of the solid electrolyte layer in the capacitor elements decreased, resulting in a decrease in the electrostatic capacitance of the solid electrolytic capacitors and an increase in ESR.
[0159] Industrial Applicability
[0160] The solid electrolytic capacitor disclosed herein has high sealing properties of the outer casing even at high temperatures, and can suppress a decrease in electrostatic capacitance and an increase in ESR. Therefore, it can be used in various applications requiring high reliability.
[0161] The present invention has been described by the currently preferred embodiments, but such disclosure is not to be construed in a limiting sense. Various modifications and changes will undoubtedly be apparent to those skilled in the art in the art to which the present invention belongs by reading the above disclosure. Therefore, the appended claims should be interpreted as including all modifications and changes without departing from the true spirit and scope of the present invention.
[0162] Description of Reference Numerals
[0163] 1: electrolytic capacitor; 2: capacitor element; 3: outer casing; 4: anode lead terminal; 5: cathode lead terminal; 6: anode body; 7: dielectric layer; 8: cathode part; 9: solid electrolyte layer; 10: cathode lead layer; 11: carbon layer; 12: silver paste layer; 13: separation layer; 14: adhesive layer.
Claims
1. A solid electrolytic capacitor comprising: a capacitor element, a lead terminal electrically connected to the capacitor element, and an outer casing sealing a portion of the lead terminal and the capacitor element, The outer casing includes a resin portion containing a resin, When the temperature at which the loss modulus measured by nanoscale dynamic viscoelasticity measurement using a nanoindentation method in the resin portion changes from increasing to decreasing is defined as the glass transition temperature Tg of the resin, the glass transition temperature Tg is 140° C. or less, In a temperature range of not less than the glass transition temperature Tg and not more than 260° C., the hardness of the resin portion measured by a nanoindentation method is not more than 0.08 GPa.
2. The solid electrolytic capacitor according to claim 1, wherein: The glass transition temperature Tg of the resin is 125° C. or lower.
3. The solid electrolytic capacitor according to claim 1, wherein: The resin is epoxy resin.
4. The solid electrolytic capacitor according to claim 1, wherein: The exterior body further includes a filler dispersed in the resin portion.
5. The solid electrolytic capacitor according to claim 4, wherein: The content of the filler in the outer casing is in the range of 75% by mass to 90% by mass.
6. The solid electrolytic capacitor according to claim 4, wherein: The maximum particle size of the filler is 55 μm or less.
7. The solid electrolytic capacitor according to any one of claims 1 to 6, wherein: The average value of the electrostatic capacitance change rate expressed by the following formula is -5.0% or more, Capacitance change rate (%) = 100 × (C1-C0) / C0 Where C0 is the initial capacitance and C1 is the capacitance after heating at 125°C for 7000 hours.
